THE EFFECT OF BRAND IDENTITY, BRAND IMAGE, AND PERCEIVED VALUE ON LOYALTY WITH CUSTOMER SATISFACTION AS MEDIATION VARIABLE FOR COSTUMER FRESH JUICE BINTARO - Farizan, Neoda; Rohman, Fatchur; Hussein, Ananda Sabil (Universitas Brawijaya, Indonesia, 2019)
This research is motivated by the opportunity to start a business by looking at opportunities among drinks-fruit drinks that have been known among the community. Marketers are required to build brand identity, brand image, perceived quality of loyalty both directly and indirectly with the level of customer satisfaction as a mediation variable on Fresh Juice Bintaro. Type of research conducted using explanatory research with survey method. The sample was 127 respondents with proportionate random sampling technique – an analytical method using PLS SEM with PLS warp software. The research instrument test included an inner model test, outer model, path diagram conversion, estimation, goodness of fit and hypothesis tester (Resampling Bootstrapping). Test the hypothesis directly using t-test. The result of the analysis shows that brand identity has no positive and significant effect on customer satisfaction and customer loyalty, brand image has a positive and significant impact on customer satisfaction and customer loyalty. Perceived value also has a positive and significant effect on customer satisfaction and customer loyalty. And customer satisfaction also has a positive and significant effect on customer loyalty.